Urethro-vesical dysfunction in progressive autonomic failure with multiple system atrophy. Issue 5 (May 1986) - Kirby, R; Fowler, C; Gosling, J; Bannister, R
Abstract : Fourteen patients with progressive autonomic failure and multiple system atrophy have been investigated by urodynamic, electromyographic and neurohistochemical means and the results compared with a series of age-matched controls. Three fundamental abnormalities of lower urinary tract function have been identified: (1) Involuntary detrusor contractions in response to bladder filling. It is suggested that these may be the result of a loss of inhibitory influences from the corpus striatum and substantia nigra. (2) Loss of the ability to initiate a voluntary micturition reflex. This may reflect the degeneration of neurons in pontine and medullary nuclei and in the sacral intermediolateral columns. In addition, these studies have demonstrated a significant reduction in the density of acetylcholinesterase-containing nerves in bladder muscle. (3) Profound urethral dysfunction. This appears to be partly due to a loss of proximal urethral sphincter tone, which causes bladder neck incompetence. In addition, the function of the striated component of the urethral sphincter is impaired. Individual motor units recorded from this muscle were clearly abnormal when compared with controls and suggested that reinnervation had occurred. We suggest that this is the result of degeneration of a specific group of sacral anterior horn cells known as Onuf's nucleus. The evidence that these particular motor units are affected, while others are spared, poses fundamental questions about the nature of selective vulnerability in degenerative diseases of the nervous system.